Exploring the role of genetic diversity and relatedness in tree seedling growth and mortality: A multi‐species study in a Bornean rain forest - Tito de Morais, C.; Kettle, Christopher J.; Philipson, C.D.; Maycock, C.R.; Burslem, David F.R.P.; Khoo, E.; Ghazoul, J. (Wiley, 2020)
Where conspecific seedlings occur at high densities, density‐dependent processes tend to depress their performance and survival relative to co‐occurring heterospecifics. We extend this observation to within‐species genetic diversity and relatedness. We posit that seedling growth and survival increase where there is higher genetic diversity, and lower relatedness, among seedling populations, under the expectation that increased genetic dissimilarity among conspecific seedlings affords greater resistance to pathogens. We used estimates of individual seedling genetic diversity (multilocus heterozygosity (sMLH)) and genetic relatedness among conspecific seedlings (pairwise kinship coefficients (LRI)), under high and low conspecific seedling density, coupled with censuses of seedling growth and mortality over 30 months to explore the role of genetic diversity and relatedness on growth and mortality of 1,485 seedlings of four dipterocarp species in an undisturbed Bornean tropical rainforest. We hypothesized that more genetically diverse and less related co‐occurring seedlings would display higher survival and growth rates. In three of our four species, lower genetic diversity increased the probability of mortality over 30 months. We observed no effect of genetic diversity on relative growth rates. Contrary to our expectations, only one species showed a negative effect of increased relatedness on mortality. In two of the four species studied, seedlings that were more genetically related to neighbouring conspecific seedlings in the sample plot were less likely to die, but grew more slowly. Synthesis. Our results confirm that genetic diversity and relatedness among seedlings shape survival probabilities differentially across species. In contrast, we found no differences in mortality and growth rates between plots with low and high seedling density. Our results suggest that a greater abundance of pollen donors could contribute to cohort seedling survival in some species, though not all, and the specific mechanisms by which genetic relatedness determines seedling demography remain uncertain. These results have conservation and management implications in view of changing patterns of gene flow in fragmented, exploited and degraded tropical rainforests, which might differentially influence natural regeneration among species.Where conspecific seedlings occur at high densities, density‐dependent processes tend to depress their performance and survival relative to co‐occurring heterospecifics. We extend this observation to within‐species genetic diversity and relatedness. We posit that seedling growth and survival increase where there is higher genetic diversity, and lower relatedness, among seedling populations, under the expectation that increased genetic dissimilarity among conspecific seedlings affords greater resistance to pathogens.We used estimates of individual seedling genetic diversity (multilocus heterozygosity (sMLH)) and genetic relatedness among conspecific seedlings (pairwise kinship coefficients (LRI)), under high and low conspecific seedling density, coupled with censuses of seedling growth and mortality over 30 months to explore the role of genetic diversity and relatedness on growth and mortality of 1,485 seedlings of four dipterocarp species in an undisturbed Bornean tropical rainforest. We hypothesized that more genetically diverse and less related co‐occurring seedlings would display higher survival and growth rates.In three of our four species, lower genetic diversity increased the probability of mortality over 30 months. We observed no effect of genetic diversity on relative growth rates. Contrary to our expectations, only one species showed a negative effect of increased relatedness on mortality. In two of the four species studied, seedlings that were more genetically related to neighbouring conspecific seedlings in the sample plot were less likely to die, but grew more slowly.Synthesis. Our results confirm that genetic diversity and relatedness among seedlings shape survival probabilities differentially across species. In contrast, we found no differences in mortality and growth rates between plots with low and high seedling density. Our results suggest that a greater abundance of pollen donors could contribute to cohort seedling survival in some species, though not all, and the specific mechanisms by which genetic relatedness determines seedling demography remain uncertain. These results have conservation and management implications in view of changing patterns of gene flow in fragmented, exploited and degraded tropical rainforests, which might differentially influence natural regeneration among species.